Trans-Pacific Partnership versus Regional Comprehensive Economic Partnership: Control of Membership and Agenda Setting - Shintaro Hamanaka (Asian Development Bank (ADB), 2014)
This paper argues that the formation of regional integration frameworks can be best understood as a dominant state's attempt to create a preferred regional framework in which it can exercise exclusive influence. In this context, it is important to observe not only which countries are included in a regional framework, but also which countries are excluded from it. For example, the distinct feature of the Trans-Pacific Partnership (TPP) is its exclusion of the People's Republic of China (PRC), and that of the Regional Comprehensive Economic Partnership (RCEP) is its exclusion of the United States. An exclusion of a particular country does not mean that the excluded country will perpetually remain outside the framework. In fact, TPP may someday include the PRC, resulting from a policy of the United States "engaging" or "socializing" the PRC rather than "balancing" against it. However, the first step of such a policy is to establish a regional framework from which the target country of engagement is excluded.
hdl:11540/2270
Keywords: F13; F15; F53; 330; free trade agreements (FTAs); Trans-Pacific Partnership (TPP); Regional Comprehensive Economic Partnership (RCEP); membership; exclusion; agenda setting